Public submission - WA State Government Climate Change Consultation - Finn, Hugh (2019)
Public submission to support the consultation undertaken by the Department of Water and Environment regarding Western Australia’s response to climate change and a proposed State Climate Policy. The submission describes the framework for a Zero Carbon Act for Western Australian to create a binding long-term emissions reduction of target of an amount of net zero greenhouse gas emissions by 2050 and a planning and budgeting process for interim 5-year carbon budgets.